PROBLEM PENETAPAN KE-TSIQAH-AN RAWI DAN KORELASINYA DENGAN KESAHIHAN RIWAYAT - muhammad, yunus (LPPM IAIN Kediri, 2024)
In hadith research, determining the tsiqah of the hadith narrator is a critical aspect that determines the validity of the hadith. The authority to assess the credibility of narrators rests largely with the jarh wa ta'dil ulama. Even though they have fulfilled the requirements for wisdom, the assessments they produce give rise to various problems. This is because the 'jarh wa ta'dil scholars are human, and it is not uncommon for their judgments to be influenced by emotions and personal relationships with certain narrators. Resulting in a sharp assessment of the narrator's tsiqah. Case studies show that personal factors such as personal animosity or disagreement can influence the determination of a company's going concern. This research examines the problems of determining the tsiqah of narrators, the results of which change due to the subjectivity of the assessor. The aim is to raise awareness so that readers can evaluate the results of the hadith critics' assessments appropriately and proportionally